1984
DOI: 10.1111/j.1365-2141.1984.tb06104.x
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal antithrombin III

Abstract: Antithrombin III (AT-III) heparin cofactor activity and its antigen levels have been determined in 106 plasma samples from 42 term and preterm neonates. In contrast to healthy adult controls, a reduced activity/antigen (act/ag) ratio (ranging from 0.26 to 0.86) was observed in 90% of the samples and was independent of the state of health of the infant. By modifying the routine assay techniques, laboratory artefacts were excluded as the cause of the observed discrepancy. The relative increase in antigenic AT-II… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
11
1

Year Published

1988
1988
2002
2002

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 25 publications
2
11
1
Order By: Relevance
“…In our material H C I I activity is lower than AT activity in both preterm and term infants. Our values for AT are somewhat higher than those found in other studies (2,3). This is because AT, in our material, is measured as activity and not as antigen concentration.…”
Section: Discussioncontrasting
confidence: 83%
See 2 more Smart Citations
“…In our material H C I I activity is lower than AT activity in both preterm and term infants. Our values for AT are somewhat higher than those found in other studies (2,3). This is because AT, in our material, is measured as activity and not as antigen concentration.…”
Section: Discussioncontrasting
confidence: 83%
“…Hypercoagulability in the newborn has been attributed to low levels of antithrombin (AT) (2). The plasma concentration of AT in the newborn is about half of that found in adults (3).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Functional activity of ATIII has been shown by Schmidt et al to be present in comparable concentrations in neonatal blood obtained from either the vein or by capillary sampling (22). Similar observations have been made by Peters et al for ATIII antigen but in this latter study, adult instead of neonatal blood was used (21). The findings of our present study concur with those of Schmidt et al in that functional activity of ATIII in the capillary sample was not significantly different from that in the venous sample; our results differ from those of Peters et al in that we demonstrated significantly higher levels of ATIII antigen in capillary samples.…”
Section: Discussionsupporting
confidence: 69%
“…To study the haemostatic status of these infants it is essential to have a set of uniform reference values of their plasma haemostatic factors. Presently available data have been derived from studies using venous blood (10-1 5), capillary blood ( I 6-18), and also mixtures of blood from both sources (19)(20)(21)(22). From the practical point of view, capillary blood sampling is relatively easy, less invasive, and should be the method of choice provided that the values of these factors in capillary samples are similar to those in venous blood.…”
mentioning
confidence: 99%